Development and Optimization of a Rapid In Vitro Micropropagation System for the Perennial Vegetable Night Lily, Hemerocallis citrina Baroni - Gaoya Zuo; Ke Li; Yining Guo; Xiaorun Niu; Lijin Yin; Zhiqiang Wu; Xiaomin Zhang; Xiaojing Cheng; Jie Yu; Shaowen Zheng; Yanfang Wang; Guoming Xing; et al. (Agronomy, 2024)
The perennial herbaceous night lily, Hemerocallis citrina Baroni, is an important vegetable crop with an increasing production and consumption in China. The long lifecycle and slow growth of the night lily are becoming bottlenecks for the large-scale production of elite lines and various genetic and breeding studies. There is a lack of a protocol for rapid and efficient micropropagation for this crop. Here, we reported the systematic investigation and optimization of in vitro plant regeneration through tissue-culture-based organogenesis in the night lily variety ‘Datong Huanghua’. We evaluated various factors affecting the efficiency of callus induction and subculture, shoot regeneration, rooting and plantlet establishment, including explant type and age, inoculation methods, basal culture media and the type and concentration of plant growth regulator (phytohormones) in various growth media. We developed an optimized protocol, as follows. The highest efficiency of callus induction was observed on Murashige and Skoog (MS) medium supplied with 22.7 µM TDZ (thidiazuron) using the young scape (flower stem or stalk) as the explant, which was cut longitudinally in half to produce a segment approximately 0.5 cm in length. Callus subculture and proliferation were more efficient on MS medium containing 9.0 µM 2,4-D (2,4-dichlorophenoxyacetic acid) under light culture conditions. Shoot regeneration showed the highest efficiency on MS medium supplemented with 8.9 µM 6-BA (6-benzylaminopurine) + 5.4 µM NAA (α-naphthaleneacetic acid), while the best rooting medium was MS medium containing 2.7 µM NAA. After transplanting, the transplanted regenerated seedlings showed the highest survival rate (96%) on a substrate mixture with a 2:1:1 ratio of peat/perlite/vermiculite. A protocol and flowchart for the rapid in vitro micropropagation of night lily plants is proposed that will facilitate various genetic, genomic and breeding studies on this crop.